Ultra scale‐down approaches to study the centrifugal harvest for viral vaccine production. Issue 5 (1st March 2018) - Melinek, Beatrice J.; Dessoy, Sandrine; Wright, Bernice; Bracewell, Dan G.; Mukhopadhyay, Tarit K.
Abstract: Large scale continuous cell‐line cultures promise greater reproducibility and efficacy for the production of influenza vaccines, and adenovirus for gene therapy. This paper seeks to use an existing validated ultra scale‐down tool, which is designed to mimic the commercial scale process environment using only milliliters of material, to provide some initial insight into the performance of the harvest step for these processes. The performance of industrial scale centrifugation and subsequent downstream process units is significantly affected by shear. The properties of these cells, in particular their shear sensitivity, may be changed considerably by production of a viral product, but literature on this is limited to date. In addition, the scale‐down tool used here has not previously been applied to the clarification of virus production processes. The results indicate that virus infected cells do not actually show any increase in sensitivity to shear, and may indeed become less shear sensitive, in a similar manner to that previously observed in old or dead cell cultures. Clarification may be most significantly dependent on the virus release mechanism, with the budding influenza virus producing a much greater decrease in clarification than the lytic, non‐enveloped adenovirus. A good match was also demonstrated to the industrial scale performance in terms of clarification, protein release, and impurity profile. Abstract : The application of a laboratory scale model to predict the performance of a disc stack centrifuge in harvesting a viral vaccine is described. The authors have established comparability of clarification and protein release, and demonstrate use of the model to provide detailed insights. This approach is cheaper, quicker, and safer than pilot scale trials, especially when applied to viral vector production.